Location, Location, Location: The Impact of Organisational Structure on Library and Information Studies Programmes. Issue 3 (3rd July 2018) - Goulding, Anne; Chawner, Brenda; Campbell-Meier, Jennifer; Calvert, Philip; Liew, Chern Li
ABSTRACT: As a discipline, library and information studies (LIS) is often considered to lack visibility and a clear identity within academia. Poor understanding of the nature of our field/discipline and our relatively small size has led to LIS programmes being partnered with a range of other subjects, located within diverse faculty structures. We suggest that this can impact on the development of both LIS curricula and research as LIS academics are brought into interdisciplinary relationships with school and faculty colleagues. The study reported here analysed the location of a sample of LIS programmes from New Zealand, Australia, the United States of America, Canada, the United Kingdom, South Africa and Singapore. Compared with previous studies, we found a higher number of 'stand-alone' schools as well as some national differences. We reflect on our experiences in a Business School, partnered with the information systems discipline, noting some key differences in boundary setting, field configuration, the use of theory in our research and links with practitioner communities. We conclude that there is a vicious circle in that the LIS discipline's lack of clear identity leads to it being partnered with disparate other fields which, in turn, further weakens its identity.